Spinning Based Source Of Iron Biscuit As Additional Food For Pregnant Women In Pulo Pakkat Village, Pulo Pakkat Puskesmas Working Area, 2021 - Tinawati Nainggolan; Rumiris Simatupang (Institute of Computer Science (IOCS), 2022)
According to WHO in 2012 it was stated that around 42% of the incidence of anemia in pregnant women in the world and an estimated 48% were in Asia, 57% in Africa, 25% in Europe and 24% in America. The purpose of this study was to make a biscuit product that is rich in iron sources based on local food in the form of spinach which is used as an additional food for pregnant women using 15 respondents for organoleptic tests and the Friedman Test was carried out to see differences in preferences for the parameters measured. The results of the descriptive organoleptic test on color showed that most of the respondents stated that the most preferred color, texture, and taste were biscuits in formula F2 (75%), while the assessment of the aroma aspect showed that most of the respondents stated that the most preferred aroma was biscuit in formula 1 (50%). In the Friedman Test with a significant level of = 0.05, the results obtained that there was no significant difference in the results of the color and aroma test and there was a significant difference in the results of the texture and taste tests owith a P value of 0.000 <0.005, meaning that spinach biscuit was effective in increasing Hb levels of pregnant women who are anemic.